Hipertiroid pada Wanita Lansia Usia 60 Tahun dengan Pendekatan Kedokteran Keluarga di Campang Raya - Josepin kevina inka wijaya; TA Larasati (CV. Jasa Sukses Abadi, 2022)
The number of people with hyperthyroidism according to the World Health Organization (WHO) worldwide in 2000 was estimated at 400 million, and it was more common in women than men with a ratio of 5: 1.7. This disease is important to be managed comprehensively because this disease is chronic so the patient must know about the disease and have the awareness to make lifestyle modifications so the treatment goals can be achieved and needs to be carried out through a family approach. This case report describes a woman Mrs. J 60 years old who was diagnosed with hyperthyroidism since 2 years ago came with complaints of heart palpitations, shaking hands, accompanied by complaints of frequent sweating even in a cold room. Mrs. J has internal risks in the form of inappropriate diet and eating habits of the patient, lack of knowledge about the causes, dangers and prevention of the disease suffered, as well as the treatment pattern of patients who only take medicine when there are complaints. External risk factors in patients, namely the lack of family support in reminding patients to manage a good lifestyle. So that pharmacological and non-pharmacological management is carried out holistically in accordance with the approach of family doctors and evidence based medicine. Enforcement of diagnosis and management of these patients has been carried out holistically, patient centered, family approach and community oriented based on several theories and recent research. In the process of behavior change, the patient has reached the trial stage.